Impact of climate change on human health (Revista Venezolana de Salud Pública, 2021)
The objective of this review was to analyze the impact of climate change and its influence on human health, which is why the outbreaks of diseases caused by climate through history, the current behavior of the problem and the actions taken were addressed. should be considered for adaptation and mitigation of adverse effects. The methodology used was the literature search published between 2004 and 2020 through the Google Scholar search engine, where journals archived in PubMed, among others, were analyzed. A matrix of terms was used in various combinations with each other, which made it possible to establish their relationship during the search. This review showed that climate change continues to affect human health, impacting their well-being, adaptability and ability to resist future threats. The modification of natural systems favors the appearance of extreme events such as hurricanes, sunami, droughts, fires, floods, bringing with it the proliferation of pathogens and vectors, generating diseases such as dengue hemorrhagic fever, malaria, increased morbidity and mortality and exacerbation of emerging diseases, so it is suggested the integral management of waste, adoption of good practices in the rational use of electricity, water, and the protection and conservation of natural heritage.
Keywords: climate change; human health; emerging diseases; vulnerable factors